2017
DOI: 10.1007/s10508-016-0929-6
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Sexual Orientation from Facial Structure: A Study with Artificial Face Models

Abstract: Research has shown that lay people can perceive sexual orientation better than chance from face stimuli. However, the relation between facial structure and sexual orientation has been scarcely examined. Recently, an extensive morphometric study on a large sample of Canadian people (Skorska, Geniole, Vrysen, McCormick, & Bogaert, 2015) identified three (in men) and four (in women) facial features as unique multivariate predictors of sexual orientation in each sex group. The present study tested the perceptual v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Thus, gendered cues facilitate detection of sexual orientation, establishing gender typicality as a valid (albeit imperfect) cue to sexual orientation cue (e.g., Freeman et al, 2010 ; Munson & Babel, 2007 ). Importantly, whereas some of these gender typicality differences may stem from biological differences (e.g., facial morphology; González-Álvarez, 2017 ; Skorska, Geniole, Vrysen, McCormick, & Bogaert, 2015 ; gait due to sexual dimorphism; Cutting, 1978 ), others rely on self-presentation (e.g., hairstyle; Krakauer & Rose, 2002 ; Rule et al, 2008 ; gait due to learned gender roles; see Johnson et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, gendered cues facilitate detection of sexual orientation, establishing gender typicality as a valid (albeit imperfect) cue to sexual orientation cue (e.g., Freeman et al, 2010 ; Munson & Babel, 2007 ). Importantly, whereas some of these gender typicality differences may stem from biological differences (e.g., facial morphology; González-Álvarez, 2017 ; Skorska, Geniole, Vrysen, McCormick, & Bogaert, 2015 ; gait due to sexual dimorphism; Cutting, 1978 ), others rely on self-presentation (e.g., hairstyle; Krakauer & Rose, 2002 ; Rule et al, 2008 ; gait due to learned gender roles; see Johnson et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The gender atypicality hypothesis suggests that gender atypical traits in homosexuals could be used as cues to indicate sexual orientation. Differences between heterosexual and homosexual individuals have thus been studied on a diverse set of traits such as face (e.g., Freeman, Johnson, Ambady, & Rule, 2010 ; González-Álvarez, 2017 ; Lyons, Lynch, Brewer, & Bruno, 2014 ; Rieger, Linsenmeier, Gygax, Garcia, & Bailey, 2010 ; Skorska, Geniole, Vrysen, McCormick, & Bogaert, 2015 ; Wang & Kosinski, 2018 ), olfaction (e.g., Sergeant, Dickins, Davies, & Griffiths, 2007 ), behavior (e.g., Ambady, Hallahan, & Conner, 1999 ; Rieger, Linsenmeier, Gygax, & Bailey, 2008 ; Valentova, Rieger, Havlicek, Linsenmeier, & Bailey, 2011 ), cognition (e.g., Neave, Menaged, & Weightman, 1999 ; Xu, Norton, & Rahman, 2017 ), and voice (e.g., Gaudio, 1994 ; Munson, McDonald, DeBoe, & White, 2006b ; Pierrehumbert, Bent, Munson, Bradlow, & Bailey, 2004 ; Rendall, Vasey, & McKenzie, 2008 ). In addition to the fact that homosexuals exhibit traits that differ from those of heterosexuals, it has been shown that some of them, such as specific neural processes (LeVay, 1991 ; Savic, Berglund, & Lindstrom, 2005 ) or specific childhood behaviors (Alanko et al, 2010 ; Bailey & Zucker, 1995 ), displayed values shifted toward those of the opposite sex, i.e., a feminization in homosexual men and a masculinization in homosexual women (Pierrehumbert et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…FaceGen was based on a face space created by PCA (Principal Components Analysis) from a dataset comprising 273 human faces that were laser-scanned in high-resolution 3D (Blanz & Vetter, 1999). This software contains age, sex and racial controls based on linear regressions on the dataset in that face space, and it has been widely used in research on face perception in high-impact publications (e.g., Cenac, Biotti, Gray, & Cook, 2019;González-Alvarez, 2017;González-Álvarez & Sos-Peña, 2022;Kihara & Takeda, 2019;Oh, Dotsch, & Todorov, 2019;Oosterhof & Todorov, 2008;Qiu & Mei, 2021;Todorov, Pakrashi, & Oosterhof, 2009).…”
Section: Methodsmentioning
confidence: 99%